A System-Wide Approach to Prevention of In-Hospital Newborn Falls. Issue 2 (March 2019) - Carr, Hester; Crotto, Joshua; Demirel, Shaban; Fisher, Stephanie; Logue, Leona; Marcott, Meghan; Miller, Lacey Rose; Mochnal, Mary; Scheans, Patricia
Abstract: Background: The Centers for Disease Control and Prevention lists accidents (unintentional injuries) as the fifth leading cause of infant mortality. Data analysis from a multihospital system of inpatient family birth centers revealed fluctuations in newborn birth admission falls rates at times above the benchmark reported in the literature. Purpose: We describe a multipronged approach to address an identified safety concern. The aim of the project was to decrease the rate of newborn falls during birth hospitalization. Despite applying multiple interventions described in the literature, newborn falls were not eliminated. Study Design and Methods: In this quality improvement project, a nursing leadership team was convened to review the literature, identify current and ideal states, obtain stakeholder input, identify contributing factors, and agree on standardized interventions to prevent newborn falls. The project received exempt status from the institutional review board. Results: Since we started the project in 2016, there was a downward trend in newborn birth admission falls in 2017; however, based on our variable data over the last 5 years and small numbers of falls, it is difficult to conclude that any one strategy or combination of strategies has been successful. Because falls from bed with the new mother were the most common types of newborn falls, interventions were focused; however, our falls rate for newborns never fell below comparable rates in the literature. Clinical Implications: More data are needed on effective interventions that can reduce the rate of newborn falls, especially those from bed while with the new mother. A comprehensive approach based on analysis of events and review of existing evidence are necessary first steps. Abstract : There has been a lot of attention to decreasing newborn falls in the inpatient setting. In this quality improvement project, after reviewing their event data and current evidence, one health system implemented a number of interventions to decrease the rate of newborn falls.